1989
DOI: 10.1038/339055a0
|View full text |Cite
|
Sign up to set email alerts
|

An autosomal transcript in skeletal muscle with homology to dystrophin

Abstract: The Duchenne muscular dystrophy (DMD) gene has been localized to chromosome Xp21 and codes for a 14-kilobase (kb) transcript and a protein called dystrophin, of relative molecular mass 427,000. Dystrophin is associated with the cytoplasmic face of muscle fibre membranes and its C-terminal domain is thought to mediate membrane attachment. Although N-terminal and central domain structures share common features with other cytoskeletal components, no significant sequence similarity between the C-terminal region of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
244
0
10

Year Published

1993
1993
2000
2000

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 468 publications
(256 citation statements)
references
References 22 publications
2
244
0
10
Order By: Relevance
“…Preliminary studies suggest that the UTRN gene has a similar, if not identical, multi-exon, structure to the DMD gene (Love et al, 1989) (unpublished data). It is not clear whether UTRN will be equally susceptible to deletions leading to protein deficiency and a t present no human disease has been associated with abnormalities a t the UTRN locus.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Preliminary studies suggest that the UTRN gene has a similar, if not identical, multi-exon, structure to the DMD gene (Love et al, 1989) (unpublished data). It is not clear whether UTRN will be equally susceptible to deletions leading to protein deficiency and a t present no human disease has been associated with abnormalities a t the UTRN locus.…”
Section: Discussionmentioning
confidence: 96%
“…The dystrophin related protein gene (the name utrophin [UTRN] was recently approved by Genome Data Base-formerly referred to as Duchenne muscular dystrophy-like [DMDL] or DRP) is an autosomal homologue of the X-linked Duchenne muscular dystrophy (DMD) gene and is localised on human chromosome 6q24 and mouse chromosome 10 (Love et al, 1989;Buckle et al, 1990;Khurana et al, 1990). The UTRN transcript is large, 13kb, and codes for a 395 kDa protein thi Man Nguyen et al, 1991; 0 1993 WILEY-LISS.…”
Section: Introductionmentioning
confidence: 99%
“…8 Utrophin is a ubiquitously expressed protein similar in amino acid sequence to dystrophin. 9,10 In adult skeletal muscle, however, it is restricted to the neuromuscular and myotendinous junctions and is thought to play a role in the maintenance of junctional folds. 11 Studies in vitro have shown that utrophin is able to bind both to actin and to the DPC.…”
mentioning
confidence: 99%
“…Further studies revealed that this gene encodes a large cytoskeletal protein highly homologous to dystrophin in its C-terminus [8] and that it presents a genomic organization similar to the structure of the dystrophin gene [9,10]. The utrophin gene is located on chromosome 6 in human and 10 in mouse [4,11].…”
Section: Introductionmentioning
confidence: 97%
“…[2,3]). In 1989, Love et al [4] showed the existence of an autosomal homologue to dystrophin subsequently named utrophin since it is expressed in a variety of tissues ( [5,6], and see for review [7]). Further studies revealed that this gene encodes a large cytoskeletal protein highly homologous to dystrophin in its C-terminus [8] and that it presents a genomic organization similar to the structure of the dystrophin gene [9,10].…”
Section: Introductionmentioning
confidence: 99%